Homeschool internship program for students’ interpersonal communication development: A descriptive study - Sary, Marisa Puspita; Bajari, Atwar; Sugiana, Dadang; Sjafirah, Nuryah Asri (International Journal of Innovative Research and Scientific Studies, 2024)
This study examined how the senior high school internship program at ABhome helped students develop their interpersonal communication skills. It employed a descriptive-qualitative method. An internship is a course requirement that gives students the opportunity to obtain practical experience at institutions or businesses to supplement their academic studies and to develop their knowledge, abilities, and attitudes. However, despite the critical necessity for the early development of interpersonal communication skills, this practice is only common at the university level in the Indonesian educational system. Interestingly, the internship program is applicable at the high school level in the homeschooling system. It employed a descriptive-qualitative method. Data were collected through in-depth interviews with eighteen students who had participated in an internship program. The interpersonal communication between students and mentors extends beyond internship-related discussions, encompassing casual conversations about various topics. The communication between students and mentors is effective for five reasons. Mentors are open to receiving input and delivering information, empathising with students, exhibiting a positive attitude, promoting respect, and demonstrating equal communication. The finding highlighted that the interpersonal communication between ABhome students and their mentors during the internship program effectively fosters qualities such as openness, empathy, supportiveness, and positivity.